Pelaksanaan Demokrasi Tanpa Norma Moral - Mukhammad Makhfudz (Faculty of Sharia and Law UIN Syarif Hidayatullah Jakarta, 2022)
There are many assumptions that state that the rules in life are only laws. Many put aside the moral norms called formal legalistic. But basically, not many understand that the true scope of law includes spiritual or theological values. So the law includes many aspects that are very complex and complicated, even as complicated as human life. Because humans are governed by laws that cover all aspects of life, not just physical but spiritual. So the law does not only belong to legal people, but belongs to everyone. The research method used in this article is a qualitative research method with an empirical juridical approach. In this paper, the author discusses leadership, democracy and the morals of a leader in carrying out their duties and responsibilities. The results of the study state that democracy in Indonesia is a political joke. Because it seems that there is a commotion that is not voiced by the people, but is carried out by individuals with certain interests. The true voice of the people is not even taken into account. So the word